Polydopamine modified charcoal loaded Fe-Cu sodium alginate microspheres and preparation method thereof

By using polydopamine-modified biochar-loaded Fe-Cu sodium alginate microspheres as the core of anaerobic ammonia oxidation sludge, the problems of sludge uplifting and nitrate by-products in the anaerobic ammonia oxidation process are solved, and the structural stability and adsorption performance of sludge are improved, ensuring efficient sewage treatment effect.

CN119774762AActive Publication Date: 2025-04-08ENVIRONMENTAL SCI RES & DESIGN INST OF ZHEJIANG PROVINCE

Patent Information

Application Number
CN202411981662.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

When treating nitrogen-containing wastewater, the anaerobic ammonia oxidation process leads to the loss of particulate sludge, affecting the treatment effect, and producing nitrate by-products, limiting the large-scale promotion of the process.

Method used

Polydopamine-modified biochar-loaded Fe-Cu sodium alginate microspheres were used as the core of the activated particulate sludge. Through the preparation of biochar, polydopamine coating, Fe-Cu ion loading and sodium alginate microsphere preparation, a stable microsphere structure was formed, which improved the structural stability and adsorption performance of the sludge.

Benefits of technology

It significantly improves the structural stability, adsorption performance and biocompatibility of the sludge, avoids excessive release of iron ions, improves the removal efficiency of nitrate by-products, and ensures the system's biodegradation efficiency and effluent water quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774762A_ABST
    Figure CN119774762A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a polydopamine modified biochar loaded Fe-Cu sodium alginate microsphere, which comprises the following steps: preparing biochar, modifying the biochar by using polydopamine, then loading the polydopamine modified biochar by using Fe-Cu, and finally obtaining the polydopamine modified biochar loaded Fe-Cu sodium alginate microsphere. According to the preparation method, the sodium alginate microspheres with different particle sizes can be prepared, the prepared sodium alginate microspheres have the function of adsorbing ammonia nitrogen, nitrate nitrogen, chlorobenzene, phosphorus, chromium ions and lead ions, the sodium alginate microspheres are used as the inner core to prepare anaerobic ammonia oxidation granular sludge, large density and good morphological support are provided for sludge particles, the problem of sludge bulking is avoided, and the anaerobic ammonia oxidation granular sludge can be prepared by using the sodium alginate microspheres as the inner core. The sewage treatment agent has the advantages that the settling performance is improved, the adsorption capacity on organic matters, ammonia nitrogen and heavy metals is enhanced, the sewage treatment effect is improved, and meanwhile, the sewage treatment agent is a biodegradable material and does not cause secondary pollution in the use process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sewage treatment, and particularly relates to polydopamine-modified biochar-loaded Fe-Cu sodium alginate microspheres and a preparation method thereof. Background Art

[0002] When using the anaerobic ammonium oxidation process to treat nitrogen-containing wastewater, anaerobic ammonium oxidizing bacteria will produce a large amount of N2 that cannot be released, forming air bags inside the granular sludge or attaching to the surface of the granular sludge, causing the density of the granular sludge to decrease, resulting in floating, and then lost with the effluent, which not only increases the mass concentration of suspended solids in the effluent, affecting the treatment effect, but also causes the system to collapse. In addition, the anaerobic ammonium oxidation process will produce about 11% of nitrate byproducts, affecting the process's emission standards. These have seriously restricted the large-scale promotion and application of the anaerobic ammonium oxidation process.

[0003] There are many studies on the characteristics of anaerobic ammonium oxidation granular sludge and the removal of nitrate byproducts in the prior art. For example, the existing patent CN201510640931.2 discloses a method for cultivating anaerobic ammonium oxidation granular sludge with a hydroxyapatite core. By adding calcium ions and high concentrations of phosphate ions to the influent, granular sludge with a hydroxyapatite core and good sedimentation performance, high mechanical strength, large particle size, and dense bacterial load can be cultivated, which can achieve efficient retention of anaerobic ammonium oxidizing bacteria at high flow rates. However, it is necessary to add calcium chloride and high concentrations of phosphate during the cultivation process. Excessive phosphate concentrations are prone to inhibit anaerobic ammonium oxidizing bacteria, and the process does not involve the deep removal of nitrate byproducts.

[0004] Although there are public documents that disclose the treatment method of adding zero-valent iron powder to the anaerobic ammonium oxidation process to remove nitrate byproducts, there are also some disadvantages and challenges: (1) Excessive release of iron ions may have a toxic effect on the microbial community, inhibit the activity of some microorganisms, and affect the biodegradation efficiency of the system. In particular, some sensitive bacteria (such as nitrifying bacteria and denitrifying bacteria) have a low tolerance to high concentrations of iron ions, which may cause the failure of important biological processes in the system. (2) The chemical properties of Fe powder in sewage may be unstable and prone to oxidation reactions to form iron hydroxide or other insoluble substances, affecting its long-term stability and effect in the particles. The dissolution and migration of iron may cause the particle structure to be destroyed, resulting in the disintegration or loosening of sludge particles. (3) Although the introduction of iron powder can improve the sedimentation performance to a certain extent, it may induce sludge bulking problems under certain conditions, especially when the iron ion concentration is high, it may cause the sludge flocs to become loose and the particle structure to be unstable. Excessive iron salts may cause the sludge to settle faster, but at the same time reduce the flexibility of the particles and make the particles fragile. In summary, although Fe powder can bring certain performance improvements in the activated granular sludge process, its introduction needs to be reasonably designed and controlled to avoid adverse effects on the system's biodegradation function, sedimentation performance and subsequent sludge disposal. Summary of the invention

[0005] In order to solve at least one of the above problems, the present invention provides a polydopamine-modified biochar loaded with Fe-Cu sodium alginate microspheres and a preparation method thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical means: The first aspect of the present invention provides a method for preparing polydopamine-modified biochar-loaded Fe-Cu sodium alginate microspheres, comprising the following steps: (1) Preparation of biochar: biomass materials are carbonized at 450-600°C in a nitrogen or inert gas environment, crushed after natural cooling, and sieved to obtain biochar powder with a particle size of 0.5-1 mm, which is then dried for later use; (2) Polydopamine coating: Disperse biochar powder in Tris buffer and disperse it evenly by ultrasound to obtain a biochar particle suspension; add dopamine in a ratio of 100 mL: 1-2 g to deionized water and stir until completely dissolved; adjust the pH to 8.5-9.0 with sodium hydroxide to obtain a dopamine solution; gradually add the dopamine solution dropwise to the biochar and monitor it with a pH meter to ensure the suitability of the reaction environment; stir at room temperature for 12-24 hours and expose to air for oxidation; when the color gradually changes from light yellow to dark brown, it indicates that the polymerization is complete and gradually deposited on the surface of the biochar particles to form a polydopamine coating; (3) Loading of Fe-Cu ions: Soak the polydopamine-modified biochar in a mixed solution of FeCl3 and CuCl2 at a ratio of 1-2 g: 20 mL and stir thoroughly for 4-6 hours; wash with deionized water and dry to obtain polydopamine-modified biochar loaded with Fe-Cu; (4) Preparation of sodium alginate microspheres: Sodium alginate is dissolved in deionized water at a ratio of 1-2 g: 50 mL, and the polydopamine-modified biochar loaded with Fe-Cu and the sodium alginate solution are evenly mixed at a ratio of 1-2 g: 100 mL; the mixed solution is dripped into the hardening liquid at a rate of 1.5-2.5 mL / min to form microspheres; the microspheres are allowed to stand in the hardening liquid for 30 min, and after hardening, they are taken out of the hardening liquid and rinsed with water to obtain polydopamine-modified biochar loaded with Fe-Cu sodium alginate microspheres.

[0007] In some embodiments of the present invention, in step (1), the biomass material is waste sludge or agricultural and forestry waste biomass.

[0008] In some embodiments of the present invention, in step (3), the mixed solution of FeCl3 and CuCl2 is prepared by mixing a FeCl3 solution with a concentration of 0.1-0.2M with a FeCl3 solution with a concentration of 0.1-0.2M.

[0009] In some embodiments of the present invention, in step (4), the hardening liquid is a calcium chloride solution with a concentration of 25-30 g / L.

[0010] In some embodiments of the present invention, in step (4), the drop distance of the mixed solution dripped into the hardening solution to form microspheres is maintained at 3-5 cm.

[0011] In some embodiments of the present invention, in steps (1) and (3), the drying conditions are 50-80° C. and the drying time is 10-15 hours.

[0012] The second aspect of the present invention provides polydopamine-modified biochar loaded with Fe-Cu sodium alginate microspheres prepared according to the method described in the first aspect.

[0013] The third aspect of the present invention provides the use of polydopamine-modified biochar-loaded Fe-Cu sodium alginate microspheres prepared according to the method described in the second aspect in the preparation of anaerobic ammonia oxidation granular sludge. The sodium alginate microspheres prepared by using polydopamine-modified activated carbon loaded with iron-copper (Fe-Cu) powder as the core of activated granular sludge (AGS) can significantly improve the structural stability, adsorption performance and biocompatibility of the sludge, and provide a slow release of iron ions to avoid microbial toxicity.

[0014] The obtained anaerobic ammonium oxidation granular sludge is applied in sewage treatment to effectively remove ammonia nitrogen, nitrate nitrogen, COD, phosphorus and heavy metal ions.

[0015] Beneficial Effects of the Invention Compared with the prior art, the present invention has the following beneficial effects: the present invention uses polydopamine (PDA) modified activated carbon loaded with iron-copper (Fe-Cu) powder to make sodium alginate (SA) microspheres. The microspheres formed by sodium alginate can firmly wrap the activated carbon and iron powder, stabilize the supporting structure, and reduce the loss of the core material. The polydopamine coating enhances the adhesion between the materials, making it difficult for the internal components of the microspheres to fall off.

[0016] The polydopamine-modified and sodium alginate-wrapped iron-copper particles slowly release iron ions, thus avoiding the inhibition of microbial activity due to excessive iron concentration. The sustained release of iron ions helps maintain good phosphorus removal performance, improves the operating stability of the system during application, and prevents the secondary release of phosphorus.

[0017] The biocompatibility of polydopamine promotes the rapid attachment and growth of microbial communities on the surface of microspheres, which can accelerate the maturation of granular sludge in applications; the porous structure on the surface of microspheres provides more attachment sites for microorganisms, promotes the formation of biofilms, and improves the organic matter degradation efficiency of the system.

[0018] The porous structure of activated carbon in sodium alginate microspheres enhances the adsorption capacity of organic matter, ammonia nitrogen and heavy metals, improving the effect of sewage treatment. The iron-copper particles wrapped with polydopamine enhance the COD degradation and phosphorus precipitation effect by catalyzing the redox reaction.

[0019] Sodium alginate and polydopamine are both biodegradable materials. They will not remain in the environment for a long time during use and have high recycling and regeneration potential, which meets the requirements of sustainable development.

[0020] When it is used as the core to prepare sludge particles, sodium alginate microspheres provide sludge particles with greater density and good morphological support, avoid sludge swelling problems, and improve sedimentation performance; this helps to form compact and stable sludge particles and improve the sedimentation rate and separation efficiency of sludge. The core structure of polydopamine-activated carbon-loaded iron-copper microspheres makes granular sludge more tolerant and able to cope with sudden organic loads or pollutant concentration fluctuations in sewage treatment; this enhanced particle stability helps to extend the operation cycle of the sludge system and reduce the frequency of shutdown maintenance. The catalytic effect of iron-copper particles can effectively promote electron transfer in the denitrification process and improve the denitrification efficiency. The synergistic effect of polydopamine and activated carbon enhances the removal of phosphorus, ensures the simultaneous removal of nitrogen and phosphorus, and improves the effluent water quality. It will not cause secondary pollution during sludge aging or disposal, which is helpful for environmental protection; the core material is easy to recycle and regenerate, and the structure of the microspheres is convenient for recovery by sedimentation or screening after sewage treatment, reducing the loss of core materials. The recovered microspheres can restore their adsorption capacity through simple regeneration treatment (such as acid washing, alkali washing, high-temperature sintering, etc.), further reducing operating costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A picture of Fe-Cu loaded polydopamine modified biochar in Example 1 of the present invention is shown; Figure 2 The pictures of Fe-Cu sodium alginate microspheres loaded with polydopamine-modified biochar of different particle sizes in Example 1 of the present invention are shown; Figure 3 The SEM image of the porous structure of the surface of Fe-Cu sodium alginate microspheres loaded with polydopamine-modified biochar in Example 1 of the present invention is shown; Figure 4 The XDR image of Fe-Cu sodium alginate microspheres loaded with polydopamine-modified biochar in Example 1 of the present invention is shown; Figure 5 The schematic diagram of the structure of the anaerobic continuous stirred reactor in Example 2 of the present invention is shown; wherein, 1, stirring reaction chamber; 2, motor; 3, stirring shaft; 4, stirring fan blades; 5, water inlet pipe; 6, water outlet pipe; 7, nitrogen pipe; Figure 6 A comparison chart of average regeneration rates of sodium alginate microspheres treated in Example 2 of the present invention under different regeneration treatment methods is shown; Figure 7 The removal effect of ammonia nitrogen after the stable activated granular sludge is formed in the reactor in Example 3 is shown; Figure 8 The removal effect of nitrate nitrogen after stable activated granular sludge is formed in the reactor in Example 3 is shown; Fig. 9A picture showing the anaerobic activated granular sludge recovered after sewage treatment in Example 3. DETAILED DESCRIPTION

[0022] The following examples are used to demonstrate preferred embodiments of the present invention. It will be appreciated by those skilled in the art that the techniques disclosed in the following examples represent techniques discovered by the inventors that can be used to implement the present invention and therefore can be considered as preferred embodiments of the present invention. However, it will be appreciated by those skilled in the art based on this specification that many modifications may be made to the specific embodiments disclosed herein and still achieve the same or similar results without departing from the spirit or scope of the present invention.

[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs, and the materials cited herein and those cited by them are incorporated by reference. Those skilled in the art will recognize or will learn through routine experimentation that there are many equivalents to the specific embodiments of the invention described herein. Such equivalents are intended to be encompassed by the claims.

[0024] The technical solution of the present application is further described in detail below in conjunction with specific implementation methods.

[0025] Example 1 Preparation of Sodium Alginate Microspheres The preparation steps of sodium alginate microspheres are as follows: (1) Preparation of biochar: Use biomass materials: waste sludge, use a tubular furnace or a high-temperature furnace, and place it in a nitrogen or inert gas environment to prevent combustion. Raise the furnace temperature to 500°C and maintain it for 3 hours to ensure complete carbonization of the biomass. Cool it naturally to room temperature. Crush the prepared biochar and use a sieve to obtain biochar powder with a particle size of 0.5-1mm to ensure uniformity. Dry it at 60°C for 12 hours to remove moisture.

[0026] (2) Polydopamine coating: The biochar powder obtained in (1) was dispersed in Tris buffer and uniformly dispersed by ultrasound to obtain a biochar particle suspension; in a 250 mL beaker, 100 mL of deionized water and 1 g of dopamine were added and stirred until completely dissolved; sodium hydroxide was used to adjust the pH to 8.5-9.0; the dopamine solution was gradually added dropwise to the biochar and monitored using a pH meter to ensure the suitability of the reaction environment; stirring was maintained for 24 hours and the mixture was exposed to air for oxidation; when the color gradually changed from light yellow to dark brown, the polymerization was completed and the mixture was gradually deposited on the surface of the biochar particles to form a polydopamine coating, thereby obtaining polydopamine-modified biochar.

[0027] (3) Loading of Fe-Cu ions: 10 g of polydopamine-modified biochar was immersed in 200 mL of a mixed solution of 0.1 M FeCl3 and 0.1 M CuCl2, stirred at 300 rpm for 2 h; washed with deionized water three times to remove unbound metal ions, and then dried at 60 °C for 12 h to obtain polydopamine-modified biochar loaded with Fe-Cu, as shown in FIG. Figure 1 shown.

[0028] (4) Preparation of sodium alginate microspheres: Dissolve 2 g of sodium alginate in 100 mL of deionized water and stir until completely dissolved. Mix 1 g of Fe-Cu-loaded polydopamine-modified biochar with the sodium alginate solution and stir thoroughly until uniform; use a dropper to drop the mixture into a hardening solution of 30 g / L calcium chloride at a rate of 2 mL / min, with the drop distance maintained at 3-5 cm to form microspheres. Let stand in the hardening solution for 30 minutes to ensure that the microspheres are completely hardened. Take the hardened microspheres out of the calcium chloride solution and wash them three times in deionized water to remove excess sodium alginate and calcium ions. Dry the washed microspheres at 60°C for 12 hours until the microspheres are completely dry. Sodium alginate microspheres loaded with Fe-Cu by polydopamine-modified biochar are obtained.

[0029] The prepared sodium alginate microspheres with different particle sizes are as follows Figure 2 As shown in the SEM image of the porous structure of the surface of sodium alginate microspheres Figure 3 As shown; XDR image of sodium alginate microspheres is as follows Figure 4 shown.

[0030] The sodium alginate microspheres prepared in this example were used to perform adsorption tests on ammonia nitrogen, nitric nitrogen, chlorobenzene, phosphorus, chromium ions and lead ions. The results are shown in Table 1 below.

[0031] Table 1 Results of ammonia nitrogen adsorption and nitric nitrogen adsorption by sodium alginate microspheres

[0032] Example 2 Cultivation of anaerobic ammonium oxidation granular sludge The steps for cultivating anaerobic ammonium-oxidizing granular sludge are as follows: (1) Take the ANAMMOX strain: Bacillus DMF-4, which was deposited in the China Center for Type Culture Collection on April 11, 2022 and has a deposit number of CGTCC No.M2022413 ( Bacillus sp.DMF-4) was activated by culturing in anaerobic medium at 30°C for 1-2 weeks; the anaerobic medium was: NH4Cl: 1000 mg / L, NaNO3: 500 mg / L, KH2PO4: 50 mg / L, KCl: 50 mg / L, NaHCO3: 100 mg / L and 2 mL / L trace element solution, among which the trace elements included: H3BO3R, MnC12, ZnSO4, Na3MoO4, H2SeO3.

[0033] (2) In an anaerobic environment, activate the ANAMMOX strain: Bacillus DMF-4 ( Bacillus sp. DMF-4) was inoculated into the culture medium at a volume fraction of 5%, and the culture medium contained 1000 mg / L NH4Cl, 500 mg / L NaNO3, 50 mg / L KH2PO4, 50 mg / L KCl, 100 mg / L NaHCO3 and trace element solution. The Fe-Cu sodium alginate microspheres loaded with polydopamine-modified biochar prepared in Example 1 were added at a mass volume fraction of 10%; (3) The sodium alginate microspheres, sludge and water obtained after the treatment in step (2) are cultured and monitored in an anaerobic continuous stirring reactor. During the culture process, the reactor is kept at a constant temperature of 30°C, and a nitrogen closed system is used to prevent air from entering, so that the reactor is in an oxygen-deficient state; the air tightness of the reactor is checked regularly, and nitrogen is supplemented when necessary to maintain an anaerobic environment. Detect NH4 in the culture medium every week + and NO3 - concentration, ensuring it is within the range of 100-1000 mg / L and 50-300 mg / L; ensure that the reactor temperature is stable and avoid fluctuations.

[0034] After continuous cultivation for 3 weeks, the anaerobic ammonium oxidation granular sludge with a sodium alginate microsphere core is obtained by collecting the sludge by gravity sedimentation or centrifugation.

[0035] Anaerobic continuous stirred reactor Figure 5 As shown, it includes a stirring reaction chamber 1, a motor 2, a stirring shaft 3 connected to the motor 2, a stirring fan blade 4 is installed at the end of the stirring shaft 3, and a water inlet pipe 5, a water outlet pipe 6, and a nitrogen pipe 7 are connected to the wall of the stirring reaction chamber 1.

[0036] The sedimentation ratio of the sludge particles is about 30%, the sedimentation time is about 6 minutes, and the degree of granulation is 91%. A series of characterization and analysis were conducted on the metal element distribution, metal valence, surface phase and crystal structure, specific surface area, magnetic saturation intensity, etc. of the sludge particles. The distribution of metal elements is shown in Table 2 below. The distribution of each element is relatively uniform and the loading condition is good.

[0037] Table 2 Distribution of metal elements in granular sludge

[0038] XRD analysis was performed and it was found that the metals and compounds were mainly FeS, CuFe2S3, (Cu,Fe)S2, FeS 2, Cu et al.

[0039] The specific surface area of ​​sludge particles is 331 m 3 g-1, total pore volume 1.72 cm 3 g-1, micropore volume 1.09 cm 3 g-1, average pore size 32 nm.

[0040] The hysteresis loop of the sludge particles was characterized, and the saturation magnetization intensity was found to be 15.62 emu g-1. The material is magnetic and has magnetic separation ability, and can be easily recycled in other water treatment processes. The microspheres after sewage treatment are recovered by sedimentation or screening, and the recovered microspheres are regenerated to restore their adsorption capacity. The average regeneration rate of the microspheres treated by acid washing, alkali washing, high temperature, cross-linking, elution and other methods is as follows: Figure 6 shown.

[0041] The results showed that the regeneration rate reached about 90% through acid washing, alkali washing, high temperature, cross-linking and other methods of regeneration, and the regeneration rate of the elution method was slightly lower, at about 70%.

[0042] Example 3 Treatment effect of anaerobic ammonium oxidation granular sludge on sewage in an anaerobic continuous stirred reactor The anaerobic ammonium oxidation granular sludge cultured in Example 2 was inoculated into Figure 3 In the stirring reaction chamber of the anaerobic continuous stirring reactor shown in the figure, sewage is connected to the reactor through the water inlet pipe. The sewage inlet index is ammonia nitrogen: 35-60 mg / L, nitrate nitrogen: 18-23 mg / L. The motor is started to stir the anaerobic ammonia oxidation granular sludge in the stirring reaction chamber to react with the sewage. During the 60 days of the reaction, the sewage is taken out of the water pipe every day for testing. The results are as follows: Figure 7 and Figure 8 shown.

[0043] The results showed that within 60 days after the sewage was treated with anaerobic ammonium oxidation granular sludge, the average removal rate of ammonia nitrogen was 91.9%; the average removal rate of nitrate nitrogen was 89%.

[0044] Anaerobic activated granular sludge recovered from sewage treatment Fig. 9 shown.

[0045] Example 4 Application of anaerobic ammonium oxidation granular sludge in sewage treatment The sewage treatment plant in an industrial park mainly receives high-ammonia nitrogen wastewater discharged by chemical companies in the park, and uses the above-mentioned anaerobic ammonium oxidation granular sludge for treatment. Influent indicators: chemical oxygen demand (COD): 200-600 mg / L, ammonia nitrogen (NH4 + -N): 300~800 mg / L, total nitrogen (TN): 400~1,000 mg / L. The key parameters are shown in the table. After 3 months of stable operation, the effluent ammonia nitrogen concentration is ≤5 mg / L, the total nitrogen removal rate is 90%, and the COD removal rate is 70%.

[0046]

[0047] This case shows that the anaerobic ammonium oxidation granular sludge has great potential in the treatment of high ammonia nitrogen wastewater, and is suitable for the denitrification needs of industrial and municipal sewage, providing a reference and reference for similar projects. This case shows that the anaerobic ammonium oxidation granular sludge has great potential in the treatment of high ammonia nitrogen wastewater, and is suitable for the denitrification needs of industrial and municipal sewage, providing a reference and reference for similar projects.

[0048] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as references separately. In addition, it should be understood that after reading the above teachings of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined in the present application.

Claims

1. A method for preparing Fe-Cu sodium alginate microspheres loaded with polydopamine-modified biochar, characterized in that: The steps include: (1) Preparation of biochar: biomass materials are carbonized at 450-600°C in a nitrogen or inert gas environment, crushed after natural cooling, and sieved to obtain biochar powder with a particle size of 0.5-1 mm, which is then dried for later use; (2) Polydopamine coating: Disperse biochar powder in Tris buffer and disperse it evenly by ultrasound to obtain a biochar particle suspension; gradually add a 1-2% mass volume ratio of dopamine solution to the biochar, stir it at room temperature for 12-24 hours, and expose it to air for oxidation. When the color gradually changes from light yellow to dark brown, it indicates that the polymerization is complete and gradually deposits on the surface of the biochar particles to form a polydopamine coating, thereby obtaining polydopamine-modified biochar; (3) Loading of Fe-Cu ions: Soak the polydopamine-modified biochar in a mixed solution of FeCl3 and CuCl2 at a ratio of 1-2 g: 20 mL and stir thoroughly for 4-6 hours; wash with deionized water and dry to obtain polydopamine-modified biochar loaded with Fe-Cu; (4) Preparation of sodium alginate microspheres: The Fe-Cu loaded polydopamine-modified biochar and a sodium alginate solution with a mass volume ratio of 2-4% are mixed evenly at a ratio of 1-2 g: 100 mL; the mixed solution is dripped into a hardening solution at a rate of 1.5-2.5 mL / min to form microspheres; the microspheres are allowed to stand in the hardening solution for 30 min, and after hardening, they are taken out of the hardening solution and rinsed with water to obtain polydopamine-modified biochar loaded with Fe-Cu sodium alginate microspheres.

2. The method for preparing Fe-Cu sodium alginate microspheres loaded with polydopamine-modified biochar according to claim 1, characterized in that: In step (1), the biomass material is waste sludge or agricultural and forestry waste biomass.

3. The method for preparing Fe-Cu sodium alginate microspheres loaded with polydopamine-modified biochar according to claim 1, characterized in that: In step (3), the mixed solution of FeCl3 and CuCl2 is prepared by mixing a FeCl3 solution with a concentration of 0.1-0.2M and a FeCl3 solution with a concentration of 0.1-0.2M.

4. The method for preparing polydopamine modified biochar loaded Fe-Cu sodium alginate microspheres according to claim 1, characterized in that: In step (4), the hardening liquid is a 25-30 g / L calcium chloride solution.

5. The method for preparing Fe-Cu sodium alginate microspheres loaded with polydopamine-modified biochar according to claim 1, characterized in that: In step (4), the drop distance of the mixed solution into the hardening solution to form microspheres is maintained at 3-5 cm.

6. The method for preparing Fe-Cu sodium alginate microspheres loaded with polydopamine-modified biochar according to claim 1, characterized in that: In steps (1) and (3), the drying condition is 50-80° C. and the drying time is 10-15 hours.

7. Polydopamine modified biochar loaded with Fe-Cu sodium alginate microspheres prepared according to the method described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Cultivation method of anammox granular sludge with hydroxyapatite core

    CN105152327B

  • Anaerobic ammoxidation sludge embedding immobilization method

    CN103408133A

  • Denitrification filter combined packing and application thereof

    CN109650560A

  • Biological composite carbon source prepared from blue-green algae and preparation process of biological composite carbon source

    CN116621320A

  • Modified biochar for heavy metal ion adsorption as well as preparation method and application of modified biochar

    CN117839658A

Cited By

  • Treatment process for domestic sewage of villages and towns

    CN120208484A

  • Preparation process of ferric salt-chitosan composite modified microbial high-adaptability biochar

    CN120866293A

  • Composite sponge carrier for anaerobic ammonia oxidation as well as preparation method and application of composite sponge carrier

    CN122403636A